(untitled) (International Journal of Physiotherapy, 2020)
Background: Sonotherapy is used in carpal tunnel syndrome (CTS) treatment; continuous or pulsed ultrasound waves are commonly used. The aim was to assess the short and long-term effects of CTS treatment using continuous and pulsed ultrasound waves. Methods: This study was a randomized clinical trial. Forty-eight patients with mild and moderate CTS (20 unilateral and 28 bilateral) were subjected to complex physiotherapy. Complex physiotherapy included whirlpool massage, neuromobilization, and sonotherapy (continuous wave and pulsed wave ultrasound). The patients were randomly placed in two treatment groups and were subjected to sonotherapy with continuous or pulsed ultrasound waves. Seventy-six hands were assessed before, immediately after, and one year after treatment. Outcome measures included the Boston Carpal Tunnel Questionnaire (CTS SSS & FSS), computer-measured global handgrip force, provocative and functional tests, assessments of vegetative disorders, and sensation disorders. Results: Significant improvements in symptoms and parameters were observed after sonotherapy in both groups immediately after and one year after treatment. Long–term effects of CTS SSS & FSS for pulsed-wave amounted to p=0.0018, p=0.0001 while p=0.0003, p=0.0021 for continuous wave, respectively. Between the groups, a statistically significant difference was found in the change of muscle strength (p=0.0374) and Luthy’s sign result (p=0.0262) between examination one and examination 3. Conclusions: Short and long-term effects of continuous and pulsed ultrasound wave in CTS treatment is comparable. Effects are influenced by energy density transmitted to tissues. Pulsed wave appears more effective in the long-term in improving the condition of hand muscles.